PENGARUH PERMAINAN PUZZLE TERHADAP KEMAMPUAN BERPIKIR KRITIS ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA SUNGAI PENUH - Thezy Meilevia Wijayanti (Jurnal Tunas Pendidikan, 2025)
Critical thingking is one of the aspects contained in tne cognitive realm. The specific aim of early childhood education is for children to be able to thing critically, give reasons, solve problems and find cause and effect relationships. For this reason, critical thingking skills really need to be taught from an early age, children learn through playing, using puzzle media to traim children’s thingking abilities. The aim of this research is to determine the effect of puzzle games on the critical thinking abilities of children aged 5-6 years at the Pembina State Kindergarten, Sungai Penuh City. This research is a type of quantitative research that uses experimental methods. This research includes Pre-Experimental Design. The population of this study consisted of 16 children. The sample for this study consisted of 16 children from the entire population who were selected using saturated sampling. The data collection technique used in this research uses observation. The data analysis technique used in this research is the t-test. Based on the research results obtained, the t table value is 1.7531, while the t value obtained is 8.91942 so t > t, this means that there is an influence of puzzle games on the critical thinking abilities of children aged 5-6 years in Pembina State Kindergarten, Sungai penuh City.